Colecistectomia laparoscópica: é possível estratificar o risco para complicações cirúrgicas baseado em associações com variáveis sociodemográficas e clínicas? - Corradi, Matheus Bartolomei de Siqueira (2019)
Cholelithiasis is the most common biliary tract disease, with a prevalence of more than 10% in the adult population. Elderly, men, diabetics and with emergency surgery present greater morbidity and mortality. The objective of this study is to associate surgical complications of laparoscopic cholecystectomies with sociodemographic and clinical data, to stratify the risk of patients with cholecystitis, to improve flow, therapeutic and surgical plans for patients with cholelithiasis and to create a Severity Score. This is a descriptive, cross-sectional, retrospective and quantitative study. Data were obtained by reviewing 2520 electronic medical records of cholecystectomized patients via the videolaparoscopic approach at the General Hospital of Carapicuiba (SP) between January 2013 and March 2017, after approval by the Research Ethics Committee. Sociodemographic and clinical variables were extracted from the medical records, besides surgical complications in order to associate them. To evaluate the independent factors correlated to the outcomes of interest, adjusted logistic regression models were proposed, where associations with p ≤ 0.05 values were considered statistically significant. Through the results it was possible to propose a Risk Stratification Model and adequacy of the patients' flows and care, in addition to creating a Severity Score. Of the 2,520 participants, 2105 were women (83.5%) and 145 (16.5%) men, with a mean age of 48.9 years. Intraoperative complications occurred in 206 patients (8.7%), being the main one the surgical convertion (3,69%), and postoperative complications in 54 (2.1%). After analyzing the complications associated with the factors, we identified that men, elderly, diabetic, patients with multiple previous surgeries and having had emergency surgery (odds ratio of 26.7) are those that presented a statistically significant difference in the non-adjusted and adjusted models complications. Complications increase significantly in the elderly with diabetes (reaching 33.1% in the 70-79 range with diabetes). In conclusion, it is possible to stratify the risk of patients with cholecystitis and, consequently, to improve the flow and therapeutic plans for the treatment of these patients. In addition, it was possible to create Severity Score based on the association between surgical complications of laparoscopic cholecystectomies and sociodemographic and clinical data